Development of a Digital Dip Coating System Based Microcontroller - Yohandri Yohandri; Khairunnisa Khairunnisa; Ramli Ramli; Rahadian Zainul (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2019)
Coating techniques are important parts in the development of nano material technology. In this paper, the development of coating technology based on microcontroller using dip coating is presented. Arduino microcontroller is implemented to control the immersion time and the speed of withdrawal of material out of the coating fluid through a stepper motor. In addition, the withdrawal speed can be digitally entered through a keypad with a value range of 0.02 mm/s to 10 mm/s. The experiment results showed the percentage of accuracy and precision of the microcontroller based dip coater was very high. Based on these results, the developed dip coater is satisfied to be used in the development of nanotech materials